2013
DOI: 10.1016/j.visres.2013.08.010
|View full text |Cite|
|
Sign up to set email alerts
|

Differential processing: Towards a unified model of direction and speed perception

Abstract: In two experiments, we demonstrate a misperception of the velocity of a random-dot stimulus moving in the presence of a static line oriented obliquely to the direction of dot motion. As shown in previous studies, the perceived direction of the dots is shifted away from the orientation of the static line, with the size of the shift varying as a function of line orientation relative to dot direction (the statically-induced direction illusion, or 'SDI'). In addition, we report a novel effect - that perceived spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
3
1
Order By: Relevance
“…The effect of rigid stripe orientation on direction perception in our experiment is a surprising new finding. Several previous studies have shown that rigid orientation cues within elongated objects or in the background are able to affect direction perception [27][28][29][30][31][32][33]. However, our study is the first to show that orientation cues within the stimulus (as opposed to elongation of the stimulus, or cues placed outside the stimulus) can affect perceived direction.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The effect of rigid stripe orientation on direction perception in our experiment is a surprising new finding. Several previous studies have shown that rigid orientation cues within elongated objects or in the background are able to affect direction perception [27][28][29][30][31][32][33]. However, our study is the first to show that orientation cues within the stimulus (as opposed to elongation of the stimulus, or cues placed outside the stimulus) can affect perceived direction.…”
Section: Discussioncontrasting
confidence: 51%
“…For example, the perceived direction of a moving line [27] or a group of moving lines [28,29] can be influenced by line orientation, and the trajectory of a dot moving in the visual periphery can be influenced by the orientation of lines in the background [30]. Similarly, static line cues placed near the stimulus have been shown to influence the perceived direction of random-dot kinematograms [31,32] and the motion of a 'barber pole' stimulus [33]. However, the effect of the orientation of a rigid striped pattern within a target, a type of stimulus that is highly relevant for the study of motion dazzle, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In another view, the perpendicularity bias is a result of Bayesian inference [11][12][13][14] , based on the fact that perpendicular angles are more likely to occur in the visual environment (for instance, trees on the horizon). Lastly, in the differential processing account 15,16 , a perpendicularity bias observed with random dot kinematograms in the context of a single tilted line was successfully modelled on the psychophysical finding that object-relative motion components (perpendicular to the line) contribute more to the perceived dot speed than non-object-relative motion components (parallel to the line) 17 .…”
Section: Local Biases Drive But Do Not Determine the Perception Of mentioning
confidence: 99%
“…The results showed that the proportional underestimation was similar across different trajectory amplitudes, although significantly larger for the smallest amplitude. The underestimation of amplitudes in the Blank condition can potentially be viewed in the light of the differential processing view on dot motion 15,16 , whereby sensitivity to non-object relative velocities is decreased.…”
Section: Experiments 2 -Isi Of Occlusionmentioning
confidence: 99%